2017
DOI: 10.4172/2168-9717.1000187
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Building Materials for Low-cost Housing and the Challenges Facing their Technological Developments: Examples and Lessons Regarding Bamboo, Earth-Block Technologies, Building Blocks of Recycled Materials, and Improved Concrete Panels

Abstract: Journal of Architectural Engineering Technology AbstractThere is a huge demand for affordable urban housing in the countries of the Global South. Using locally available and/or produced building materials for housing can reduce the buildings impact on the environment. Climate conditions and natural disaster risks, which differ by region, determine the applicability of the sustainable building materials and building structures. This article focuses on five groups of building materials: bamboo, compressed earth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 2 publications
(3 reference statements)
0
36
0
3
Order By: Relevance
“…In Central America, CTCs contribute to the upgrading of housing and habitats in association with housing cooperatives. In an investigation of 22 housing cooperatives in Central America, it was found that the cooperatives were founded on the housing model with mutual aid, a proven model of the Uruguayan Federation of Housing Cooperatives with Mutual Aid (FUCVAM), for solving a substantial part of the housing deficit in Uruguay [6]. The key features of such a model are affordability and quality housing, the use of group savings, joint actions and efforts, and common property in the form of land and homes.…”
Section: Central America: Ctcs For Housing Cooperativesmentioning
confidence: 99%
See 2 more Smart Citations
“…In Central America, CTCs contribute to the upgrading of housing and habitats in association with housing cooperatives. In an investigation of 22 housing cooperatives in Central America, it was found that the cooperatives were founded on the housing model with mutual aid, a proven model of the Uruguayan Federation of Housing Cooperatives with Mutual Aid (FUCVAM), for solving a substantial part of the housing deficit in Uruguay [6]. The key features of such a model are affordability and quality housing, the use of group savings, joint actions and efforts, and common property in the form of land and homes.…”
Section: Central America: Ctcs For Housing Cooperativesmentioning
confidence: 99%
“…Following this CTC model, another was built in the nearby housing cooperative Juntando Manos. We Effect, a Swedish NGO, and Foundation Juan XXIII, a Spanish NGO, provided loan aid to these housing cooperatives [6].…”
Section: Nicaraguamentioning
confidence: 99%
See 1 more Smart Citation
“…While perception on structural quality and soundness of LIH requires a full cycle analysis by structural engineers, a perception survey or opinion of residents/occupiers can also provide a good sense of the structural sturdiness of LIH as viewed by the occupants/residents. LIH envisages the conception and deployment of advanced and appropriate budgeting, cost reduction, building and construction techniques through use of locally available materials and the prudent application of skills and technologies without compromising the housing units' strength, performance and life of the structure (Bredenoord, 2017;Foong et al, 2017;Ganiyu, 2016;Holweg, 2007;Howell, 2011;Tam, 2011;Salem et al, 2006;Van Damme and Houben, 2018). Overall, approximately 10% of LIH RDP or state subsidised structures perceive such structures as either having structural defects or inadequacies with respect to walls and roofs.…”
Section: Metropolitan or City Area In South Africa Type Of Dwellingmentioning
confidence: 99%
“…Construction with industrial materials such as concrete or bricks is often considered as a plausible solution, but traditional materials and processes may offer interesting alternatives. Traditional buildings are commonly built by households and/or local communities themselves (Schroeder 2016;Bredenoord 2017), thus saving on labour costs. Therefore, material costs become the major contribution to the expense.…”
Section: Introductionmentioning
confidence: 99%